Just energy transition in coal regions: Innovative framework for assessing territorial just transition plans - M. Peretto; W. Eichhammer; D. Süsser (Renewable and Sustainable Energy Transition)
Coal regions are particularly vulnerable to the plans to reduce regional pollution and move towards a climate-neutral economy. The European Union therefore supports the transition away from coal in those regions that are socio-economically most affected to reduce negative impacts for communities. Coal regions have developed their Territorial Just Transition Plans (TJTPs); however, it is unclear which impacts the plans should address to ensure a just transition and to what degree. To address this gap, the following research aims to develop an indicator and impact matrix to assess the extent to which TJTPs address key impacts related to just transitions and how are these quantified. Key just transition impacts were investigated quantitatively and qualitatively in six coal regions. The results indicate that the expected transition impacts on communities in coal regions are mainly negative. Furthermore, it was also found that TJTPs predominantly address the impacts on employment and the environment, whereas social and demographic impacts are less comprehensively considered. These deficiencies should be addressed in each region in order to define tailored policies and investments that can assist in minimising negative impacts and capitalising on positive benefits for communities. The proposed approach can facilitate a more precise definition and assessment of regional impacts of transition towards climate neutrality, thereby aiding the identification of policy areas and measures that will enable the implementation of a truly just transition.